Rice Production Forecasting System in East Java Using Double Exponential Smoothing Method - Siti Nurul Afiyah; Fajar Kurniawan; Nur Lailatul Aqromi (Universitas Muhammadiyah Sidoarjo, 2021)
. Rice (Orza savita L.) is one of the most important carbohydrate-producing food plants in the world, besides wheat and corn. The need for rice continues to increase because the increase in the number of consumers is not balanced with sufficient production. According to BPS (2017), rice production in East Java Province in 2017 amounted to 13.06 million tons of Dry Milled Grain (GKG). The aim of this research is to predict / forecast the yield of rice production in the next period in order to become the target of rice production in the next period. The raised problem is how to predict the rice production. From the data that has been obtained from 1993 to 2017 the data shows increasing gradually which is classified into trend data. Thus, the forecasting method that can be used is the double exponential smoothing method. In the calculation process, it is done by finding S ', S' ', a, b & also the next period of forecasting sessions, using 0 <x <1. From the calculation of alpha 0.1 - 0.9 obtained the smallest MAPE of 3.14 in alpha 0.5. The results of the forecast for the next period increased 13299827.49 tons with an accuracy of 96.86%.